Analisa Performansi Sistem Air Conditioning Mobil tipe ET 450 dengan Variasi Tekanan Kerja Kompresor - Purnawan, Adi; -, Suarnadwipa; Wirawan, I K.G. (Jurnal Energi Dan Manufaktur; Vol 4, No.1 April 2010, 2012)
Comfort and coolness when traveling by vehicle especially car is highly needed. So many attempts have been made byhumans that comfortable traveling by car can be achieved. One of the effective ways in which comfortable traveling by car can beobtained is by installing air conditioning. The performance of air conditioning system is highly influenced by how the compressorworks. In other words, the pressure resulting from the suction highly determines the performance of air conditioning system,which then affects how the compressor works, the compressor power, the refrigeration effect, the efficiency of isentropic andcoefficient of performance (COP) of the car air conditioning sytem especially that of the car air conditioner type ET 450. Fromwhat has been described above, the writer would like to conduct a research entiled “ Analysis of the Performance of the Car AirConditioning system Type ET 450 with Variation of the Compressor Pressure”.The test was conducted on the car air conditioner type ET 450 with variations of suction 2.8 bar, 3 bar, 3.2 bar, 3.4bar, 3.6 bar and 3.8 bar. The data were obtained from the pressure of compressor output (P2), the temperatures in each point areT1, T2, T3, T4, the compressor rotationn is n, the strength of electrical current is I, and the volumetric flow rate. The data werethen processed and analyzed so that so that the performance of each variation of the suction could be actually and theoreticallyobtained.The findings show that the bigger the suction, the bigger the performance of the car air conditioner type ET 450 wouldbe. The theoretical coefficient of performance (COP) produced was bigger than the actual COP. The optimal COP took placewhen the suction was 441.325 kPa, the actual COP was 3.513177 and the theoretical COP was 3.632062
Keywords: Performance, air conditioning, compressor pressure (suction).